Superovulation And Egg Recovery In Goats - Haji Yusoff, Rosnina (1989)
Research on superovulation , egg recovery and embryo transfer in goats has been conducted in many developed countries of the world , but similar studies in tropical goats are limited in South-East Asia . There fore a study was undertaken to determine if the indigenous goat, Kambing kacang , and their crosses could be superovulated and eggs recovered by techniques previously reported for goats in the temperate zone. A total of 70 Kambing kacang does were super ovulated with either Pregnant Mare Serum Gonadotroph in ( PMSG ) or Follicle Stimulating Hormone ( FSH-P ) . PMSG (500, 1000 and 1500 i . u ) was administered in tramuscularly as a single dose , two days before the withdrawal of 60 mg medroxyprogesterone acetate intravaginal sponges. FSH-P (19 ,IS.and 20mg) was divided into four decreasing daily doses ( 4,3,2,1; 6,4,3,2; 8,6,4,2 mg ) and administered subcutaneously at 0700 h and 1900 h .